An Improved Projection Method for Determination of Fatigue Parameters of Metal Structures Based on Spherical Direction Cosine Group Construction - Yang, B.; Ma, B.Q.; Wu, Y.Y.; Chen, B.; Xiao, S.N.; Yang, G.W.; Zhu, T. (Проблемы прочности, 2016)
The key components of railway rolling stock are almost constantly in the multiaxial stress state in service. To evaluate the fatigue strength of the structure, stress parameters should be obtained beforehand. The traditional projection method assumes that the maximum principal stress is the maximum tensile stress, and then the projection process is performed without taking the tension/ compression states of principal stresses into account. To address these inadequacies, a method for fatigue parameter determination was proposed based on principal stress projection toward a spherical direction cosine group. This method can determine the direction of maximum tensile stress and preserve the tension/compression attribute of stress during calculating the maximum stress and the minimum stress. Therefore, the physical meaning of present improved method is more apparent than the traditional projection method, and its algorithm is simple and effective. The fatigue strength assessments of a welded bogie frame were performed utilizing the traditional projection method and present method respectively. Results show that some maximum stresses calculated by the improved method could be 19.4% higher than those obtained by the traditional one at some nodes, while the minimum stresses and the stress ratio deduced from these two methods could even be of opposite sign. The present method, which takes the tension/compression properties of principal stresses into consideration, is more reasonable, as compared with the traditional projection method, and thus the fatigue strength assessment results are more credible.